SHIELDING THE NEXT GENERATION: A QUALITATIVE ANALYSIS OF TOBACCO CONTROL POLICIES FOR KARACHI’S MINORS - Jonathan Johnson; Wafa Aftab; Romaina Iqbal; Narjis Rizvi; Rubeka Mansha; Fazila Thawer; Zeeshan Aslam (Policy Research Journal, 2025)
The global tobacco epidemic remains one of the most severe public health crises, causing over 8 million deaths annually, including from second-hand smoke exposure. Tobacco use is the most preventable cause of illness and death worldwide, with smoking being the most common method. Adolescents are particularly vulnerable, with smoking often beginning before age 21. This study explores the current status and challenges of tobacco control policy implementation for minors in Karachi, Pakistan. Using a qualitative exploratory approach, insights were gathered from policymakers and implementers. The findings reveal significant barriers to effective policy enforcement, including socioeconomic factors, peer pressure, and insufficient legislative action. The study concludes that stronger local, national, and global tobacco control policies are essential, particularly those aimed at protecting minors. Improved public health efforts, education, and awareness programs are recommended to reduce tobacco use and its harmful effects on children and adolescents.